Old and New Threats of Organised Crime - SINN, Arndt; P. IDEN, Marcel (Sécurité Globale, 2022)
Alongside terrorism, organised crime (OC) constitutes one of the two focal points of many contemporary security strategies. The common understanding of organised crime is that of a tightly knit hierarchical structure dominated by a small group of leaders, held together by strict discipline with a its own set of rules and united by a common regional origin. Legendary examples of this type of organised criminal groups are the Italian mafia such as the ‘Ndrangheta, the Camorra and the Cosa Nostra, but also groups from Albania, the Chinese Triads or the Japanese Yakuza. Their main avenues of income, according to common belief, are the illicit trade with weapons, the global drug markets and human trafficking. However, apart from the conventional perspective on organised crime, there exist more aspects of the phenomenon that evade the initial glance. Ranging from decentralised networks conducting cyberattacks to groups or networks engaging in product counterfeit, environmental crimes or illicit medial products, organised crime is a multifaceted phenomenon.